Of artwork, court files, and lullabies (Communications Psychology)
Communications Psychology promotes psychological research that reaches beyond its boundaries. Empirical Work can speak to psychological theory and constructs or explore psychological processes using any of a vast array of data and analysis methods. Whether a study belongs in Communications Psychology does not depend on the type of data that are used; but on whether the data are of high quality, appropriately analyzed, and can answer the psychological research question.